2010
DOI: 10.1016/j.fertnstert.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of adiponectin in reproduction: from polycystic ovary syndrome to assisted reproduction

Abstract: Objective To summarize the effects of the adipokine adiponectin on the reproductive endocrine system, from the hypothalamic-pituitary axis to the gonads and target tissues of the reproductive system. Design A Medline computer search was performed to identify relevant articles. Setting Research institution. Intervention(s) None. Result(s) Adiponectin is a hormone secreted by adipose tissue that acts to reduce insulin resistance and atherogenic damage, but it also exerts actions in other tissues. Adipone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 115 publications
1
83
0
7
Order By: Relevance
“…Studies have shown that both leptin and adiponectin can regulate the hypothalamic pituitary gonadal axis independently, as well as synergistically through their interactions with each other and with other metabolically active hormones [11,18]. Specifically at the level of the human ovary, adipocytokines are implicated in the regulation of steroidogenesis by modulating the action of insulin and insulin like growth factor 1 (IGF-1) [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that both leptin and adiponectin can regulate the hypothalamic pituitary gonadal axis independently, as well as synergistically through their interactions with each other and with other metabolically active hormones [11,18]. Specifically at the level of the human ovary, adipocytokines are implicated in the regulation of steroidogenesis by modulating the action of insulin and insulin like growth factor 1 (IGF-1) [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its actions in peripheral tissues, adiponectin reportedly contributes to the central regulation of food intake and energy homeostasis ) as well as reproduction (Budak et al 2006;Michalakis and Segars 2010). Metabolic state and reproductive capacity are known to interact.…”
Section: Introductionmentioning
confidence: 99%
“…En effet, l'adiponectine, AdipoR1 et AdipoR2 et la résistine sont présentes dans l'hypothalamus et l'hypophyse chez l'homme et les rongeurs (pour revue voir [18]). Des études in vitro montrent que l'adiponectine, en activant l'AMPK, réduit la sécrétion in vitro de GnRH (gonadotropin releasing hormone) par les cellules hypothalamiques GT1-7.…”
Section: Rôle De L'adiponectine Et De La Résistine Dans Les Fonctionsunclassified
“…Une étude récente indique que l'expression d'AdipoR1 et AdipoR2 est diminuée (60 %) dans l'endomètre des femmes en échec d'implantation après une procédure de FIV (fécondation in vitro) pour infertilité comparée à l'expression dans l'endomètre de femmes fertiles [38]. D'autre part, les taux plasmatiques d'adiponectine sont fortement diminués chez des patientes atteintes de diabète gestationnel, du syndrome des ovaires polykystiques (SOPK), mais aussi d'endométriose et de cancer de l'endomètre (voir [18]). Ces études suggèrent qu'une modification de l'expression de l'adiponectine et/ou de ses récepteurs pourrait être impliquée dans la réceptivité endométriale [38,39].…”
Section: Rôle De L'adiponectine Et De La Résistine Au Cours De L'implunclassified